Multiwavelength study of RX J2015.6+3711: a magnetic cataclysmic variable with a 2-h spin period. Issue 2 (28th December 2015) - Coti Zelati, F.; Rea, N.; Campana, S.; de Martino, D.; Papitto, A.; Safi-Harb, S.; Torres, D. F.
Abstract : The X-ray source RX J2015.6+3711 was discovered by ROSAT in 1996 and recently proposed to be a cataclysmic variable (CV). Here, we report on an XMM–Newton  observation of RX J2015.6+3711 performed in 2014, where we detected a coherent X-ray modulation at a period of 7196 ± 11 s and discovered other significant (>6σ) small-amplitude periodicities which we interpret as the CV spin period and the sidebands of a possible ∼12-h periodicity, respectively. The 0.3–10 keV spectrum can be described by a power law (Γ = 1.15 ± 0.04) with a complex absorption pattern, a broad emission feature at 6.60 ± 0.01 keV, and an unabsorbed flux of (3.16 ± 0.05) × 10 −12 erg cm −2  s −1 . We observed a significant spectral variability along the spin phase, which can be ascribed mainly to changes in the density of a partial absorber and the power law normalization. Archival X-ray observations carried out by the Chandra satellite, and two simultaneous X-ray and UV/optical pointings with Swift, revealed a gradual fading of the source in the soft X-rays over the last 13 yr, and a rather stable X-ray-to-optical flux ratio ( F X / F V ≈ 1.4–1.7). Based on all these properties, we identify this source with a magnetic CV, most probably of the intermediate polar type. The 2-h spin period makes RX J2015.6+3711,  the second slowest rotator of the class, after RX J0524+4244 ('Paloma'; P spin  ∼ 2.3 h). Although we cannot unambiguously establish the true orbital period with these observations, RX J2015.6+3711 appears to be a key system in the evolution of magnetic CVs.